ANALISIS PERAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN KALIMANTAN BARAT - B01109118, Saripto (Jurnal Pembangunan dan Pemerataan, 2014)
Determination retrieval research is motivated by the agricultural sector as the largest sector in the GDP contribution in West Kalimantan. However, the welfare of farmers is still not too large compared to other sectors. The purpose of the research was to determine the superior sub-sector in agriculture, employment and the welfare of farmers in West Kalimantan in 2008-2012. Analytical tool used to measure the sector and sub-sector superior is location quotient (LQ) and to measure the level welfare of farmers is exchange rate farmers (NTP). The results showed that in West Kalimantan agriculture sector superiore, sub-sectors is superior feed crops with LQ=1,31, plantation crops with LQ=1,14 and livestock with LQ=1,05 than any other region in the island of Borneo. Agricultural sector employment is the largest of all sectors, well above half the amount of labor employed with median 61,51%. From the three sub-sectors superior only the plantation sub-sector capable of prospering of farmers, that is comprised of horticulture crops with NTP 103.25 and plantation crops with 115.62. While the two sub-sectors of superior feed crops with NTP 96,61 and livestock NTP 88,19, farmers have not been able to prosper of the indicated by exchange rate farmers (NTP), because the larger the index to be paid than the index of prices received of farmers. Even sub-sectors such as fisheries is not superior capable of prospering of farmers with NTP 105,28. The level of general welfare of farmers increased to 101.81, or 1.02 fold the ratio in 2007. Plantation sub-sector that is capable of prospering farmer, which is comprised of horticulture crops with NTP 103.25 and 115.62 smallholder crops. Sub-sector superior feed corps with NTP 96.61 and livestock with NTP 88.19, has not been able to prosper the farmers. Even sub-sectors such as fisheries is not superior capable of prospering farmer with NTP 105.28. Keywords: Superior Sectors, Employment, Welfare Farmers